2016
DOI: 10.3847/0004-637x/821/2/113
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Formation in Action: Characterizing Accelerated Galaxy Evolution in Compact Groups Using Whole-Sky Wise Data

Abstract: Compact groups provide an environment to study the growth of galaxies amid multiple prolonged interactions. With their dense galaxy concentrations and relatively low velocity dispersions, compact groups mimic the conditions of hierarchical galaxy assembly. Compact group galaxies are known to show a bimodality in Spitzer IRAC infrared color space: galaxies are preferentially either quiescent with low specific star formation rates (SSFRs) or prolifically forming stars-galaxies with moderate levels of specific st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…This high density combined with low velocity dispersions (Hickson et al 1992) in many cases leads them to exhibit multiple physical processes associated with galaxy-galaxy interactions: tidal tails and bridges visible optically, in atomic gas (H i), or both (e.g. Verdes-Montenegro et al 1997;Sulentic et al 2001;Verdes-Montenegro et al 2005a;Serra et al 2013;Konstantopoulos et al 2013); intragroup diffuse X-ray emission (Belsole et al 2003;Desjardins et al 2013;O'Sullivan et al 2014a); shock excitation from starburst winds or galaxy-tidal debris collisions (Rich et al 2010;Vogt et al 2013;Cluver et al 2013); anomalous star formation (SF) activity, molecular gas content and morphological transformations (Tzanavaris et al 2010;Plauchu-Frayn et al 2012;Alatalo et al 2015;Eigenthaler et al 2015;Zucker et al 2016;Lisenfeld et al 2017), among others.…”
Section: Introductionmentioning
confidence: 99%
“…This high density combined with low velocity dispersions (Hickson et al 1992) in many cases leads them to exhibit multiple physical processes associated with galaxy-galaxy interactions: tidal tails and bridges visible optically, in atomic gas (H i), or both (e.g. Verdes-Montenegro et al 1997;Sulentic et al 2001;Verdes-Montenegro et al 2005a;Serra et al 2013;Konstantopoulos et al 2013); intragroup diffuse X-ray emission (Belsole et al 2003;Desjardins et al 2013;O'Sullivan et al 2014a); shock excitation from starburst winds or galaxy-tidal debris collisions (Rich et al 2010;Vogt et al 2013;Cluver et al 2013); anomalous star formation (SF) activity, molecular gas content and morphological transformations (Tzanavaris et al 2010;Plauchu-Frayn et al 2012;Alatalo et al 2015;Eigenthaler et al 2015;Zucker et al 2016;Lisenfeld et al 2017), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Lisenfeld et al (2016) in preparation and H 2 masses calculated from CO observations (Leon et al 1998;Verdes-Montenegro et al 1998;Martinez-Badenes et al 2012;Lisenfeld et al 2014), using X CO =2× 10 20 cm −2 (K km s −1 ) −1 . HCG galaxiesspan the range of f mol values, suggestive of their large range of properties and environments (Bitsakis et al 2010(Bitsakis et al , 2011Zucker et al 2016). Many HCGs contain warm H 2 -luminous galaxies, known to host shocks (Cluver et al 2013), which may be a better comparison sample with CO-SPOGs than interactions.…”
Section: The Molecular Gas Fraction Of Co-spogsmentioning
confidence: 99%
“…Specifically, galaxies that reside in CGs exhibit a "canyon" in infrared color space that implies a rapid transition between relatively actively star-forming and quiescent systems. Curiously, it should be noted that this transition region in infrared color space corresponds to the optical "red sequence" rather than the "green valley" (Walker et al 2013;Zucker et al 2016), indicating that a distinct evolutionary process is taking place in CGs. In other words, the infrared transition region seen in CGs, is not seen in comparison samples and should not be confused with the optical green valley.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that the CG environment has an impact on galaxy evolution that is not seen in several other environments, including field galaxies, isolated pairwise mergers, and galaxy clusters (Johnson et al 2007;Tzanavaris et al 2010;Walker et al 2010Walker et al , 2012Lenkić et al 2016;Zucker et al 2016). Specifically, galaxies that reside in CGs exhibit a "canyon" in infrared color space that implies a rapid transition between relatively actively star-forming and quiescent systems.…”
Section: Introductionmentioning
confidence: 99%